Irrigation and organic and mineral fertilization in sunflower crop - Gomes, Krishna Ribeiro; Viana, Thales Vinícius de Araújo; Sousa, Geocleber Gomes de; Costa, Fellype Rodrigo Barroso; Azevedo, Benito Moreira de (Comunicata Scientiae, 2018)
The amount of available water to certain crops can play a direct influence on the expected effect of the application of fertilizers, whether mineral or organic origin. Thus, this work was performed in order to evaluate the effects of the application of different irrigation depths and organic and mineral fertilizers in the development and production of sunflower plants in Ceará state, Brazil. The experiment was carried out in full sun in pots containing Alfisol, in a completely randomized experimental design with a 5 x 3 factorial, five irrigation depths (L1 = 50%, L2 = 75%, L3 = 100%, L4 and L5 = 125% = 150% of the Class-A Tank evaporation ECA) and three fertilizations (F1 = organic, using aerobic fermentation of Bovine biofertilizer, F2 = mineral fertilizers, NPK-based and F3 = control without an addition of fertilizers with five replications. At 65 days after sowing (DAS), the following characteristics were analyzed: number of leaves, stem diameter, and plant height. In the maximum development of achenes (about 90 DAS), the plants were harvested to determine the head diameter, dry mass of 1000 seeds, dry mass of sunflower head, seed dry mass and crop yield. The different depths applied causing a significant effect in all the sunflower crop yield parameters being as low as the effect of the applied lower depth. The application of biofertilizers in plants provided increments similar to those provided by the application of mineral fertilizers in stem diameter, dry mass of the sunflower head, the head diameter and seed dry mass under different irrigation depths. Since most applied irrigation depth (150% of the ECA), combined with the mineral fertilizer and bovine biofertilizer provided higher results in sunflower production.